THE REFLECTION OF BRITISH CULTURAL VALUES, SOCIAL INDICATORS, AND LANGUAGE USE IN JOJO MOYES’S WORKS - Tursunova Marxabo Raxmonovna (International Journal of Literature and Language Studies, 2026)
Annotation. This article analyzes the artistic expression of British cultural realities, social markers, and linguistic units in the novels of English writer Jojo Moyes. Specifically, through the analysis of her novels "Me Before You," "After You," "One Plus One," and "The Giver of Stars," the article examines class distinctions, speech etiquette, daily life realities, gender stereotypes, and the interpretation of cultural codes from the perspective of translation studies. Comparative-contrastive, contextual-component, and linguocultural analysis methods are employed. As a result, it is determined that in Jojo Moyes' works, national and cultural units not only create the background but also serve as tools for revealing character traits and generating cognitive dissonance.